Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: If x^(1/6) = 6, then √x^6 is ? [#permalink]
01 Apr 2012, 06:20

Expert's post

TomB wrote:

bunnel

how did you come x=6^6,please explain

because to cancel out your root you have to raise the same to the exponent of the same and at the same time raise the other part of the equation.

For instance: if you have √x= 4 rise to power of 2 both side; so you'll have x=16 or 3√x=4 then you'll have x=64 (rise to power of 3).

So we have x=6^6; of course in our case we do not need to obtain 6^6 (46656). we care about to substitute this value to our x and then resolve our problem. It was simple but me too was confused looking at the problem.

I ask to Bunuel to correct me if I'm wrong.
_________________

KUDOS is the good manner to help the entire community.

Last edited by carcass on 01 Apr 2012, 08:23, edited 1 time in total.

Re: If x^(1/6) = 6, then √x^6 is ? [#permalink]
06 Jun 2013, 06:20

In such cases i always try to find some simple number for which i am sure and make simple but similar calculation. For example in our case we have x^(1/6)=6 from a glance it is difficult to get what is this number, but if we take \sqrt{x}=2 we see that x is 4, because x^1/2=2 is the same as to say 2 multiplied by itself once. In our case we have x^(1/6)=6 using our logic that means x=6^6. In the second expression we have (x^6)^1/2 ---> (x)^6*1/2=x^3

Now the easiest part, since we know that x=6^6 then x^3=(6^6)^3=6^18

Answer choice D.
_________________

If you found my post useful and/or interesting - you are welcome to give kudos!